Ambiente interno : a participação e o envolvimento das pessoas na busca do diferencial competitivo - Peruffo, Gilberto (2001)
Day after day, even small companies and multinationals brands need to compete in a worldwide market. All kind of global strategies have to involve production and regional market knowledge. Still being essential for company have a complete view of it market and it right position to gain competitive advantage. In a global market, get possible for the companies be in touch with last generation technologies and equipment's and all kind of research. Companies like that should develop products focused in customer's desire, even those extremely strict. Specifically in our country, as hard as we could think, the companies have access to credit lines, to the fiscal incentives offered by the states that alliance with the market potential are making possible the appearance of a lot companies and the growth of the companies already existent. However, these resources alone don't produce results to the company if it doesn't possess an internal organization able to assimilate the new market situation. The companies have to be able to apply the maximum resources offered by new technologies and understand how a communications facility means solution for many internal problems. In short terms, technology, financial resources, research and knowledge are available, however, the human resources might be prepared and developed in order to become the whole knowledge in profits. According 'JURAN' and his Total Quality Control philosophy the human resources playing fundamental role in the process, and in my opinion a company is something like a ship where all must be prepared to hold the rudder. I will develop a basic job looking for productivity and company's development through the people's involvement, focused in process of motivation, creativity and staff valorization. I believe that there no good production process without those requirements. Based on real case of a automotive parts and foundry company, located in Bento Gonçalves - RS, this work will look for to organize it mainly in its Industrial Division, adopting in participate administration where, through a information system and personnel involvement we will seek all favorable conditions to politics and strategies in get the growth of company.